2013
DOI: 10.1093/rfs/hht035
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Diversifiable Risk in Venture Capital and Private Equity

Abstract: Entrepreneurship, VC and IPOs for their comments. We are grateful to The Eugene M. Lang Entrepreneurship Center for financial support. Special thanks go to Jesse Reyes and Thomson Venture Economics, who provided the Venture Economics data and to Maryam Haque and Brendan Hughes of Dow Jones who provided LP Source. All errors are our own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 48 publications
(44 reference statements)
1
53
1
Order By: Relevance
“…Kaplan and Schoar (2005) analyzed fund-level data and found that the net-of-fee returns of private equity funds (both venture capital and buyout) approximately equal the return on the S&P 500, whereas Ljungqvist and Richardson (2003), using a different sample, documented returns that are 5.7% higher than a simulated investment in the S&P 500 over the same time frame. Ewens, Jones, and Rhodes-Kropf (2013) used general partner value estimates (rather than realized returns) to estimate quarterly private equity returns and documented annual alphas of 4% for buyout funds. Phalippou and Gottschalg (2009) used a dataset similar to that of Kaplan and Schoar (2005) but argued that reasonable adjustments to the data to reflect the nature of reporting biases lead to lower estimates of returns.…”
Section: Performance Of Alternative Investmentsmentioning
confidence: 99%
“…Kaplan and Schoar (2005) analyzed fund-level data and found that the net-of-fee returns of private equity funds (both venture capital and buyout) approximately equal the return on the S&P 500, whereas Ljungqvist and Richardson (2003), using a different sample, documented returns that are 5.7% higher than a simulated investment in the S&P 500 over the same time frame. Ewens, Jones, and Rhodes-Kropf (2013) used general partner value estimates (rather than realized returns) to estimate quarterly private equity returns and documented annual alphas of 4% for buyout funds. Phalippou and Gottschalg (2009) used a dataset similar to that of Kaplan and Schoar (2005) but argued that reasonable adjustments to the data to reflect the nature of reporting biases lead to lower estimates of returns.…”
Section: Performance Of Alternative Investmentsmentioning
confidence: 99%
“…Ewens et al () examine US data from 1980 to 2007 and find that the betas of VC and BO are 1.24 and 0.72, respectively. Ljungqvist and Richardson () analyse portfolio companies and report that BO's portfolio beta average is 1.08, while the VC's average beta is 1.12.…”
Section: Discussionmentioning
confidence: 99%
“…The volatility of private equity during the 1994–2012 period is 24.4%, which is above the stock market volatility of 19.0% over the 1926–2012 period – which is expected since private equity funds typically hold non‐diversified portfolios with high idiosyncratic volatility (cf. Ewens, Jones, & Rhodes‐Kropf, ).…”
Section: Datamentioning
confidence: 99%